2013
DOI: 10.5114/ceji.2013.37755
|View full text |Cite
|
Sign up to set email alerts
|

Toll-like receptors 3 ligation directly and indirectly affects mast cell cysteinyl leukotriene generation

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 31 publications
(60 reference statements)
0
1
0
Order By: Relevance
“…Only TLR2, TLR3, and TLR4 proteins were found in mast cells from isolated human nasal polyps [22], murine peritoneal cavity [38], and FSMC [30]. Our previous studies have shown that freshly isolated rat peritoneal mast cells express both surface TLR2 and TLR4 molecules [20, 39], as well as TLR3 and TLR7 surface proteins [40, 41]. In this study we evaluated the expression of TLR receptors in native fully mature rat mast cells freshly isolated from the peritoneal cavity, that is connective tissue type mast cells.…”
Section: Discussionmentioning
confidence: 99%
“…Only TLR2, TLR3, and TLR4 proteins were found in mast cells from isolated human nasal polyps [22], murine peritoneal cavity [38], and FSMC [30]. Our previous studies have shown that freshly isolated rat peritoneal mast cells express both surface TLR2 and TLR4 molecules [20, 39], as well as TLR3 and TLR7 surface proteins [40, 41]. In this study we evaluated the expression of TLR receptors in native fully mature rat mast cells freshly isolated from the peritoneal cavity, that is connective tissue type mast cells.…”
Section: Discussionmentioning
confidence: 99%